A New Modified Experimental Meibomian Gland Injury Model: Partial Loss of Gland Due to Orifice Cauterization and the Alleviating Potential of 22-Oxacalcitriol - Jin, Kai (J Clin Med, 2020)
1α,-25-dihydroxy-22-oxacalcitriol (maxacalcitol) is a non-calcemic vitamin D3 analog clinically approved to treat psoriasis, and its role has been increasingly recognized in suppressing keratinocyte proliferation, mediating inflammation, and regulating the immune response. A large number of studies have suggested that vitamin D plays an important role in maintaining ocular surface health. However, its topical effects on the Meibomian gland (MG) has been insufficiently investigated. Here, we introduce an experimental MG orifice injury model, where the partial glandular loss occurred after electrical cauterization on a limited number of MG orifices, and investigate the efficacy and safety of maxacalcitol ointment in treating this MG orifice injury model. We confirm the alleviation of MG atrophy and ductal dilation by maxacalcitol ointment application. The recovery of injured MG visualizing as the residual MG area is significantly better in the maxacalcitol group (p = 0.020) compared with the Vaseline(®) group, especially during the first two weeks. The cornea and other ocular tissues were not affected by maxacalcitol ointment application during our two-month observation period. Altogether, this work indicates that maxacalcitol has therapeutic potential in the amelioration of initial injury of MG orifices caused by electrocautery.